Produção de fibras de carbono por solution blow spinning usando poliacrilonitrila (PAN) como precursor - Lopes, Caio Matheus de Souza (2024)
Industrially, using polyacrylonitrile (PAN) as a precursor for carbon fiber production is the most common method, and the process of obtaining it typically involves either melt spinning or solution spinning. However, concerning the production of micrometer-sized fibers, other methods stand out, such as electrospinning, which involves applying a potential difference between the solution and the target, causing the solvent to evaporate and form fibers. Another emerging technique is solution blow spinning (SBS), which enables the production of carbon fibers with higher productivity, smaller fiber diameters, and greater flexibility in solvent selection. In this study, SBS was employed to produce carbon fibers using PAN as the polymer matrix and polyvinylpyrrolidone (PVP) as a roughness agent on the fiber surface, at concentrations of 0, 2.5, 5, and 10% relative to the PAN mass. The polymer injection rate was 3 ml/hr, compressed air pressure was 20 Psi, working distance was 20 cm, and collector rotation speed was 600 rpm. After spinning, the fibers underwent two annealing curves in a muffle furnace, first from room temperature to 100 °C, and then to 260 °C, both at a rate of 3 °C/min with a 2-hour hold. Subsequently, they were carbonized in a nitrogen atmosphere at a rate of 5 °C/min from room temperature to 1000 °C, where they remained for 2 hours. The obtained carbon fibers were characterized by morphological, structural, and elemental analyses to better understand their behavior. Scanning electron microscopy (SEM) analysis confirmed fiber formation and the maintenance of the fibrous structure even after carbonization. Using Raman spectroscopy, the values of the D band (disorder) and G band (graphitic) were obtained, from which the ID/IG ratio was calculated to determine the R factor (ID/IG), indicating an increase in graphitization with the addition of PVP. Increasing PVP content resulted in a decrease in the ID/IG ratio (0.9518, 0.9464, 0.9143, 0.8897), indicating greater structural regularity with increasing PVP content. Elemental CHN analysis confirmed the presence of carbon and nitrogen even after carbonization, and Fourier-transform infrared (FTIR) spectroscopy revealed fiber cyclization due to the appearance of the peak at 2115 cm-1, corresponding to the isocyanate group, and the absence of the peak at 2249 cm-1 corresponding to the C≡N group. However, carbon fibers were successfully obtained using the SBS technique, employing PAN as a precursor and PVP as a roughness agent on the fiber surface in a nitrogen atmosphere.